Induced Defense in Ryegrass–Epichloë Symbiosis Against Listronotus bonariensis: Impact on Peramine Levels and Pest Performance - Manuel Chacón-Fuentes; Gunnary León-Finalé; Marcelo Lizama; Gastón Gutiérrez-Gamboa; Daniel Martínez-Cisterna; Andrés Quiroz; Leonardo Bardehle (Journal of Fungi)
The Argentine stem weevil (ASW), a major pest in ryegrass pastures, causes significant agricultural losses. Ryegrass can establish a symbiotic association with Epichloë endophytic fungi, which supply chemical defenses, including peramine. This symbiosis helps protect ryegrass by providing peramine, which acts as a primary defense. In addition, ryegrass can activate induced defense mechanisms, with peramine remaining the central agent in response to herbivorous insect attacks. Therefore, this study assessed the feeding of the ASW on ryegrass carrying endophytic fungus and peramine levels in aerial organs and its effects on pest performance. Argentine stem weevil adults and larvae were placed on ryegrass leaves and stems to assess feeding. Two treatments were used: endophyte-free plants and endophyte-colonized plants. After ASW feeding damage, insect consumption was measured by the leaf area consumed. To evaluate peramine production and its increase in response to ASW attack, peramine levels in leaves were analyzed using liquid chromatography. Damaged E+ ryegrass plants showed significant increases in peramine, with adult and larval herbivory raising levels by 291% and 216% in stems and by 135% and 85% in leaves, respectively, compared to controls. Endophyte-free (E−) plants experienced more ASW damage, as insects preferred feeding on them, showing reduced activity as peramine levels rose in endophyte-infected (E+) plants. An oviposition assay confirmed insect preference for endophyte-free (E−) plants. Additionally, larvae reared on endophyte-infected (E+) plants had lower survival rates, correlating negatively with peramine levels. These results emphasize peramine’s role in strengthening ryegrass defenses against ASW, impacting both feeding and larval development.